Analisis Kebertahanan Hidup Orang Asli Papua Pada Aspek Infrastruktur di Permukiman Kumuh Kelurahan Klawalu Kota Sorong - Marshush, Ummi Hanifah; Murni, Murni; Nabila, Nabila; Fitriyanti, Fitriyanti (Jurnal Pembangunan Nagari; Vol 11 No 1 (2026)DO - 10.30559/jpn.v6i11.797, 2026)
Development in the land of Papua, particularly in terms of housing provision, often still places Indigenous Papuans (OAP) in a marginalized position. In Sorong City, many OAP live in slum settlements, one of which is located in Klawalu sub-district. The slum settlements are not fully equipped with basic infrastructure. However, they continue to live and survive in these conditions. The purpose of this study is to explore how OAP survive in the slum settlements of Klawalu sub-district despite in adequate infrastructure. This research was conducted using a qualitative approach, with phenomenology analytical method. The results show that there are several strategies by OAP to survive, including self-help efforts in providing infrastructure particularly in creating access to houses located in swamp area, adapting to the environment, seeking alternatives and strategies to meet needs such as lighting, electricity networks, clean water, and sanitation, the advantages of their stilt house structure, local wisdom, sharing energy resources, and receiving assistance from the government. Local wisdom that needs to be maintained is a very strong attitude of closeness and kinship, an attitude of solidarity of local leaders, an active and open mind towards the planning programs that the government wants to carry out. To improve the quality of life of OAP, it is necessary to develop and improve basic infrastructure.